PENGARUH BERBAGAI KONSENTRASI LARUTAN IRIGASI SODIUM HIPOKLORIT KOMBINASI OMEPRAZOLE 8,5% SEBAGAI ANTIBAKTERI Enterococcus faecalis - , MARIA SANTINIARATRI, drg. Wigyo Hadriyanto, M.S., Sp.KG(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Omeprazole is one of proton-pump inhibitor which when combined with sodium hypochlorite (NaOCl) inherits a superior antibacterial efficacy against Enterococcus faecalis. Eradication of Enterococcus faecalis bacteria is important to achieve a successful root canal treatment. The objective of this study is to figure out the effectiveness of various concentrations of NaOCl combined with 8.5% Omeprazole as an antibacterial efficacy against Enterococcus faecalis. Suspension of Enterococcus faecalis was made in 108 CFU/ml concentration and then inoculated in Mueller Hinton Agar (MHA) medium. There were 7 petri dishes containing MHA medium used in this study, each of dish was implemented by six pits with 6 mm diameter and 3 mm depth. Each of petri dish was filled with each treatment group in 5 pits and 1 other pit was filled with aquades as negative control, solution volume drops was applied by 50 Î¼l. Seven examined treatment groups were 0.5% NaOCl, 2.5% NaOCl, 5.25% NaOCl, 0.5% NaOCl combined with 8.5% Omeprazole, 2.5% NaOCl combined with 8.5% Omeprazole, 5.25% NaOCl combined with 8.5% Omeprazole, and 8.5% Omeprazole itself as positive control. The mediums above were incubated for 24 hours at 37Â°C. Inhibition zone were measured by sliding caliper in accuracy of 0.02 mm. Data were analyzed by one way Anava and followed by LSD test. Test results generated by one way Anava and followed by LSD test showed that there were significant effects occurred (p < 0.05). This study concluded that the addition of 8.5% Omeprazole increased the antibacterial efficacy of NaOCl against Enterococcus faecalis.